Nurse‐Authored Patents and Their Influencing Factors Analysis Among Oncology Nurses Based on the Structural Equation Model - Hong Yang; Zhichao Feng; Wen Li; Yuhan Lu (Nursing Open)
ABSTRACT Aims This study analysed the status of nurse‐authored patents and their influencing factors. In particular, this study examined the effects of nurses' innovative behaviour and creative self‐efficacy on nurse‐authored patent output via structural equation modelling (SEM). Design A descriptive cross‐sectional study. Methods Nurses were recruited from one tertiary cancer hospital in Beijing, China. Among them, 352 oncology nurses completed the online versions of the Nurse Innovative Behavior Scale and Creative Self‐Efficacy Scale in 2023. Results We collected a total of 332 valid questionnaires. Fifty‐seven (17.2%) nurses had 1–3 patents, and only 6 (1.8%) had more than three patents. The final model revealed a chain reaction between creative self‐efficacy, innovation behaviour and nurse‐authored patent output (χ2 = 11.962, df = 7, p = 0.102). Significant differences were observed in the number of nurse‐authored patents and based on age, educational profile, professional title, length of service, position, participation in science and technology innovation training, and experience in project presentation (all p < 0.05). Conclusion Nurses still play a minor role in the field of medical technology innovation. It is necessary to promote innovative behaviour among nurses and improve their creative self‐efficacy in terms of innovation. Impact Developing intervention strategies to encourage nurses to pursue clinical innovations is crucial for nursing managers and technological innovation promoters.